The Evolution of Public Debt Vulnerabilities In Lower Income Economies. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2020)
Public debt in lower-income economies (LIEs) has risen in recent years, with half of the countries covered in this report now assessed to be at high risk of or already in debt distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet